2022
DOI: 10.1016/j.scitotenv.2022.153310
|View full text |Cite
|
Sign up to set email alerts
|

Heatstroke-related ambulance dispatch risk before and during COVID-19 pandemic: Subgroup analysis by age, severity, and incident place

Abstract: Background In summer 2020 under the COVID-19 pandemic, the Ministry of Health, Labour and Welfare has made public warnings that specific preventive measures such as maskwearing, stay-at-home orders, may increase heatstroke risk. In our previous work, we found a lower risk of heatstroke-related ambulance dispatches (HSAD) during the COVID-19 period, however, it is uncertain whether similar risk reductions can be observed in different vulnerable subgroups. This study aimed to determine the HSAD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Aging is one of the risk factors for stroke and low PA in the elderly. [ 41 ] Considering the influence of gender and age, this study found that with the increase of age, the risk of stroke in the middle-aged and elderly people became higher and higher, but the level of PA became lower and lower. A previous study found that the number of women who died of stroke was lower than that of men, but the age-specific incidence of women and men was similar under the age of 55.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is one of the risk factors for stroke and low PA in the elderly. [ 41 ] Considering the influence of gender and age, this study found that with the increase of age, the risk of stroke in the middle-aged and elderly people became higher and higher, but the level of PA became lower and lower. A previous study found that the number of women who died of stroke was lower than that of men, but the age-specific incidence of women and men was similar under the age of 55.…”
Section: Discussionmentioning
confidence: 99%